A new species of Argiope (Araneae: Araneidae) from Brazil - Motta, Paulo César (2009)
ABSTRACT: A new species of Argiope Audouin, 1826 is described. This is a large Argiope from South America and is found mainly in "cerrado" vegetation in central Brazil. Argiope legionis sp. nov. is most similar to A. ericae LEVI, 2004 but differs from this species by the coloration and epigynum in the female and the median apophysis and embolus of the palpus in the male palp.